Implementation of Machine Learning on Android Based Application for Classifying the Types of Injuries on Traffic Accident: Implementasi Machine Learning Menggunakan Aplikasi Android untuk Klasifikasi Jenis Luka Cedera pada Kecelakaan Lalu Lintas - Naury, Chairullah; Hastomo, Mursid Dwi; Saputra, Dhuha Ardha; Yovian, Vincent (Politeknik Assalaam Surakarta, 2025)
This research implements a machine learning model to classify the types of injuries sustained in road accidents. Accidents can happen anywhere and at unexpected times, and not many drivers know how to provide first aid in the event of an accident. These problems encourage researchers to carry out machine learning-based research that can provide recommendations for action and first aid materials/equipment, as well as information on the nearest health facilities to facilitate the search for help in an emergency. The machine learning model created uses a variety of training datasets in the form of a set of images of road accident injuries. The transfer learning method is used to classify injuries and road conditions. The preliminary results of the machine learning model showed promising application potential, as evidenced by the relatively high retention rate and successful classification results. The implementation of machine learning can contribute to increased safety awareness and proactive measures to reduce road accidents and injuries.